Phosphatidylserine binding directly regulates TIM-3 function. Issue 17 (17th September 2021) - Smith, Courtney M.; Li, Alice; Krishnamurthy, Nithya; Lemmon, Mark A.
Abstract : Co-signaling receptors for the T cell receptor (TCR) are important therapeutic targets, with blockade of co-inhibitory receptors such as PD-1 now central in immuno-oncology. Advancing additional therapeutic immune modulation approaches requires understanding ligand regulation of other co-signaling receptors. One poorly understood potential therapeutic target is TIM-3 (T cell immunoglobulin and mucin domain containing-3). Which of TIM-3's several proposed regulatory ligands is/are relevant for signaling is unclear, and different studies have reported TIM-3 as a co-inhibitory or co-stimulatory receptor in T cells. Here, we show that TIM-3 promotes NF-κB signaling and IL-2 secretion following TCR stimulation in Jurkat cells, and that this activity is regulated by binding to phosphatidylserine (PS). TIM-3 signaling is stimulated by PS exposed constitutively in cultured Jurkat cells, and can be blocked by mutating the PS-binding site or by occluding this site with an antibody. We also find that TIM-3 signaling alters CD28 phosphorylation. Our findings clarify the importance of PS as a functional TIM-3 ligand, and may inform the future exploitation of TIM-3 as a therapeutic target.